Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173863
|View full text |Cite
|
Sign up to set email alerts
|

Communication Behavior in Embodied Virtual Reality

Abstract: Embodied virtual reality faithfully renders users' movements onto an avatar in a virtual 3D environment, supporting nuanced nonverbal behavior alongside verbal communication. To investigate communication behavior within this medium, we had 30 dyads complete two tasks using a shared visual workspace: negotiating an apartment layout and placing model furniture on an apartment floor plan. Dyads completed both tasks under three different conditions: face-to-face, embodied VR with visible full-body avatars, and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(66 citation statements)
references
References 34 publications
3
58
1
Order By: Relevance
“…The non-verbal communication behavior is usually presented in the mutual conversion through face-to-face, video conferencing [Whittaker 2003] or embodied avatar in VR [Dodds et al 2011;Fabri et al 2002;Roth et al 2018;Smith and Neff 2018]. The non-verbal cues delivered by the virtual characters in the collaborative virtual environment influence the efficiency of task performance [Roth et al 2018;Smith and Neff 2018]. The mirror is usually used in the singleuser scenario [Collingwoode-Williams et al 2017;Kilteni et al 2013;Maister et al 2015] to evaluate the communication behavior such as non-verbal cue.…”
Section: Communication Behavior In Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-verbal communication behavior is usually presented in the mutual conversion through face-to-face, video conferencing [Whittaker 2003] or embodied avatar in VR [Dodds et al 2011;Fabri et al 2002;Roth et al 2018;Smith and Neff 2018]. The non-verbal cues delivered by the virtual characters in the collaborative virtual environment influence the efficiency of task performance [Roth et al 2018;Smith and Neff 2018]. The mirror is usually used in the singleuser scenario [Collingwoode-Williams et al 2017;Kilteni et al 2013;Maister et al 2015] to evaluate the communication behavior such as non-verbal cue.…”
Section: Communication Behavior In Vrmentioning
confidence: 99%
“…With modern tracking technology, NVC is generally implemented for the player through a virtual character whose behavior is captured by peripheral devices. The user can view the virtual world through the avatar's eyes, and avatar movement reflects their own body movement [Smith and Neff 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple previous studies have explored the adaptation of a virtual body [Slater et al 2010], and argued for the human flexibility to adapt non-human avatars [Won et al 2015]. User embodiment, in turn, can lead to higher social presence ratings, comparable to face-to-face interactions [Smith and Neff 2018]. With regard to augmented communication in virtual environments, Gerhard et al [2001] explored hybrid human/agent communication models to allow for continuous presence in educational virtual environments.…”
Section: Introductionmentioning
confidence: 99%
“…Smith and Neff evaluated participants' communication behavior in VR, and found that using full-body avatars provided a high level of social presence and that the participants' conversation patterns were very similar to those shown in face-to-face conditions [13]. The results indicate that our AR tele-guidance system has similar capabilities.…”
Section: Introductionmentioning
confidence: 75%